Environmental Fate, Biological Interactions, and Toxicity Mechanisms of Engineered Nanoparticles (ENPs) - Christina M. Brenckman; Ashish D. Borgaonkar; William H. Pennock; Genoa R. Warner; Jay N. Meegoda (International Journal of Environmental Research and Public Health, 2026)
Engineered nanoparticles (ENPs) are being used with increasing frequency in industrial and consumer products across applications in industry, agriculture, ecology, and biomedicine. The unique physicochemical characteristics that make nanoparticles desirable in product design also affect their fate in the environment, interactions with living systems, and mechanisms of toxicity. Traditional testing methods and toxicological paradigms based on dissolved chemicals are poorly suited to understand ENP risks, primarily due to their small size, large SA:Vs, increased reactivity, and a surface chemistry that can be tuned during synthesis. Nanoparticle toxicity is dependent on complex relationships between particle characteristics, transformations in the environment, resulting exposure scenarios, and biological effects. Here we review ENP toxicity across a property → transformation → exposure → toxicity continuum, with a focus on how particle properties affect environmental and biological transformations relevant to toxicity. Properties such as size, shape, surface chemistry, dissolution, redox activity, and aggregation propensity are reviewed with respect to effects on transport and bioavailability, cellular uptake, biodistribution, and toxicity mechanisms. Transformations including aggregation, oxidation, dissolution/sulfidation, aging and eco-corona formation are discussed with regard to impacts on exposure and risk. Finally, major mechanisms of toxicity including oxidative stress, ion toxicity, membrane damage, inflammation, and genotoxicity are discussed with regard to nano–bio interactions. Analytical challenges associated with studying ENPs, shortcomings of the current risk assessment methods, and emerging Safe-by-Design approaches are also reviewed. Furthermore, connections between the fields of engineered nanoparticle toxicology and microplastics/nanoplastics are discussed, with particular focus on overlapping physicochemical properties, transformations, exposures, and biological mechanisms.